ANALISIS BUDAYA ORGANISASI PADA PERUSAHAAN APM OTOMOTIF DI INDONESIA (STUDI KASUS PADA PT. XYZ) - Pebri Tutur Srihadi; Ferdinand Dehoutman Saragih (Inovbiz: Jurnal Inovasi Bisnis, 2019)
This study aims to understand the organizational culture in one of the automotive companies in Indonesia as well as to study the level of readiness of the company in the application of organizational culture to face the highly competitive automotive business in Indonesia. Organizational culture that represents a set of value, trust and shared meaning that is applied intensively and institutionalizes will provide collective benefits that can make the organizational culture strong which will give of success to the company where success of organization depend on organizational culture because organizational culture is the most important construct in building and maintaining a company's success.This study discusses the mapping of organizational culture in one of the automotive companies in Indonesia based on the Denison cultural organization model that has four dimensions, namely mission, consistency, involvement and adaptability. The sample of 174 aimed at employees in all divisions and in all hierarchy in the company.The results of the study show that the company has a strong culture in each division of work and hierarchical companies. The company has a model that fits the four-dimensional model of Denison's Corporate culture, making the company consider having capabilities that are in line with competition in the automotive industry in Indonesia.